A Research Study on Historical Preservation and Urban Renewal of the Bund - Huang Xiaoying (Lodz University of Technology Press, 2023)
The Bund became the first area of urbanization in Shanghai in 1843. After experiencing the golden construction era in the 1930s, it formed a unique urban form of ‘high-density enclosed blocks’. In recent years, with the focus of Shanghai's urban development shifting to urban renewal, the Bund area is also gradually entering a new urban renewal cycle, facing challenges for space expansion and functional improvement, and facing the problem of mutual restriction between historical preservation and spatial growth. Therefore, in the renewal process of the Bund area, it is necessary not only to meet the spatial growth brought by the changing functions, but also to maintain its unique historical urban form and morphological characteristics. It is urgent in this cycle to establish a more targeted and operable framework of historical preservation to balance and stabilize the impact and changes brought by the renewal and development projects in the historical area. This study will take the Bund as the research object, review the historical process of its urban form and the formation of its urban spatial morphological characteristics, take ‘block-street-building’ as the research framework, analyse its multi-level spatial morphological characteristic elements, and establish its historical protection framework in the process of urban renewal. Further, this study will take the renewal projects of three blocks in the Bund area as a case study, analysing how the historical preservation framework could play an effective role in the renewal process, so as to deal with the uncertainty of development projects in various scattered blocks, and to maintain the stability and continuity of the urban form of the Bund historical area.
Keywords: the bund; historical preservation; urban renewal; urban form; wał; ochrona zabytków; rewitalizacja urbanistyczna; forma urbanistyczna